PENERAPAN MODEL PEMBELAJARAN KOOPERATIF LEARNING PADA MATERI MENGANALISIS PEMENTASAN DRAMA BAGI KELAS XI TKJ1 SMK NEGERI NGAMBON - Sutardi; Ahmad Rizqulillah Khoiruz Zadit Taqwa (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2023)
This study aims to describe the application of the cooperative learning model to analyze drama performances for grade XI students, as well as to evaluate teacher activities, student activities, and student learning outcomes. The method used was qualitative descriptive research, each consisting of planning, implementation, observation, and reflection stages. The instruments used included observation sheets of teacher and student activities, as well as learning outcome tests. The research subjects were 11th-grade students at a high school. The results showed that: (1) teacher activity increased significantly from cycle I to cycle II, with indicators such as providing clear instructions, group management, and more effective feedback; (2) student activity also increased, marked by active participation in discussions, group collaboration, and the ability to express opinions; and (3) student learning outcomes showed an improvement from the adequate to good category. Thus, the cooperative learning model proved effective in improving the quality of learning to analyze drama performances